Union formation under conditions of uncertainty: The objective and subjective sides of employment uncertainty - Bonalo, Danilo; Vignoli, Daniele (My University, 2021)
BACKGROUND The link between economic forces and family dynamics has received renewed attention in the present era of heightened uncertainty. Economic uncertainty has usually been linked to unfavorable labor market circumstances, such as unemployment and short-term contracts. Nonetheless, union formation may also be affected by subjective appraisals of employment conditions, including employment security and – acknowledging the prospective nature of uncertainty itself – expectations of future employment. OBJECTIVE This study seeks to empirically disentangle the effects of the objective and subjective sides of individual employment uncertainty on the entry into union. METHODS We apply event history techniques to longitudinal data taken from the Household, Income and Labour Dynamics in Australia (HILDA) survey to examine whether and how objective measures of employment uncertainty (labor market status and contract type) and subjective measures (employment security and employment expectations) are associated with entry into a first union. RESULTS Our results show that objective markers of employment uncertainty – unemployment or temporary (casual) jobs – inhibit entry into a union for both men and women. Furthermore, different appraisals of employment uncertainty affect union formation across employment conditions. When individuals face objective employment uncertainty while still expecting their employment situation to improve, either by exiting unemployment (in particular among men) or retaining their jobs (among both sexes), union formation is not necessarily postponed. CONTRIBUTION We stress the importance of considering how different future expectations influence family formation across different levels of objective uncertainty. The sole use of objective markers of employment uncertainty provides only a partial, and possibly inaccurate, perspective on union formation: the specter of the future also matters.
Demographic Research
Keywords: Labour market